2019
DOI: 10.1016/j.otsr.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of arthroscopy for managing coxa profunda

Abstract: Coxa profunda is a complex entity that can result in femoro-acetabular impingement (FAI). A meticulous evaluation of the type of acetabular overcoverage is essential to determine which treatment is best suited to each individual patient. Focal overcoverage with no posterior impingement can be treated by arthroscopic recontouring of the disproportionate acetabular wall. Any femoral deformities should be managed during the same procedure. General overcoverage, with predominant postero-inferior impingement, requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Across the literature, indications and limitations of postless technique are seldom discussed. The utility of postless distraction for patients who require greater traction force, such as patients with coxa profunda or other challenging bone anatomy, is unknown 2 , 3 , 7 , 13 . For this reason, Mei-Dan et al's observation that less than 1% of hips are undistractable using postless technique is difficult to generalize to patients with deep hips 2 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Across the literature, indications and limitations of postless technique are seldom discussed. The utility of postless distraction for patients who require greater traction force, such as patients with coxa profunda or other challenging bone anatomy, is unknown 2 , 3 , 7 , 13 . For this reason, Mei-Dan et al's observation that less than 1% of hips are undistractable using postless technique is difficult to generalize to patients with deep hips 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In evaluating postless systems, Kollmorgen et al indicated weight as a disadvantage for patients under 120 lbs 4 , suggesting that weight may limit the traction force attainable. Because patients with coxa profunda are likely to require more traction force during hip arthroscopy 7 , additional studies are necessary to quantify the force required and provide guidance for the use of postless distraction on patients with deep hips.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations